Kajian Numerik Infiltrasi Flue Gas pada Komponen Lance Tube Soot Blower Tipe PS-SL - Haidar Ali Yafie M; Shah Muhammad; Moballa Burniadi (Proceedings Conference on Marine Engineering and its Application, 2018)
One failure that often occurs in the sootblower is that it breaks in the lance tube caused by corrosion. Based on the results of the root analysis the failure of the cause of corrosion in the component lance tube is caused by the occurrence of flue gas infiltration which results in blockage of the vent valve. This causes the remaining blowing medium cannot be pushed into the furnace and if left for too long will cause condensation in the lance tube. Condensation mixed with corrosive substances from flue gas can accelerate the corrosion rate on the lance tube. The simulation was carried out using the CFD (Computational Fluid Dynamics) method assisted by Fluent ANSYS 17.2 software. Corrosive substances in flue gas are modeled as inert particles of fly ash using DPM (Discrete Phase Model). To overcome the infiltration problem, angular variations were made in the converging section of the under-expanded nozzle on the lance tube. The concentration of DPM particles is compared to the cross section to find out how many corrosive particles enter the soot blower. Particle concentrations at angles of 10º 15º and 20º are 2,043 kg/m³, 0.515 kg/m³, 0475 kg/m³, respectively. While the mass fraction is 0.0069, 0.0017, 0.0016, respectively. The simulation results show a reduction in infiltration with the addition of an angle to the nozzle, with an angle of 20º showing the best results.